Perbandingan Metode CBIA dan FGD dalam Peningkatan Pengetahuan dan Ketepatan Caregiver dalam Upaya Swamedikasi Demam pada Anak - Marianti Avi Lathifah; Susanti; Much Ilham; Aji Wibowo (Universitas Indonesia, 2015)
Self medications which are often applied to children are including coughs, colds, flu, and nasal congestion (17.2%), fever (15%), headache (14%), diarrhea and abdominal pain (9%). The results from previous studies showed only 0.4% caregiver of 4-6 years old children in Banyumas Regency did self medication correctly in children's fever. The aim of this study was to determine the influence of Community Based Interactive Approach (CBIA) and Focus Group Discussion (FGD) methods for improving knowledge and correctness of caregivers in children's fever self medication. We conducted quasi experimental design with a control group of non random pretest and posttest. Results of Wilcoxon test showed that there were significant differences of knowledge statistically before and after treatment using FGD (p < 0.05) and CBIA (p < 0.05), while for correctness before and after treatment with FGD and CBIA methods, there were no statistically significant difference in FGD (p > 0.05) and CBIA (p > 0.05). The difference of mean score in FGD group (2.45) was greater than CBIA group (0.96) with p<0.05. However there was no significant difference between FGD and CBIA methods in improving the correctness (p>0.05). In conclusion, FGD method was better in improving the knowledge compared with CBIA method, but not for the correctness of self medication in children's fever.